Implementasi Wakaf Dalam Persfektif Ekonomi Syari’ah, Fiqih Kontemporer dan Etika Bisnis Islam - Nia Pususpita Hapsari; Anna Herliana; Luqman Hakim; Khaerunnisa (Jurnal Manajemen DIVERSIFIKASI, 2025)
Waqf symbolizes a social, and economic institution or body that has a useful and meaningful contribution to the welfare of humanity and the Islamic nation economically, socially, and religiously. Implementing waqf means that modern environmental conditions seek to interpret comprehensive knowledge from various perspectives: Sharia economics, contemporary fiqh, and Islamic ethics. This article aims to analyze the implementation of waqf in these three perspectives and to convey a more comprehensive picture and perception regarding the relevance, and contribution of waqf in terms of economic development and the welfare of the community. With a theoretical approach, this article tries to explore the potential of waqf in improving community welfare under Sharia principles. The research methods use qualitative, from the understanding of social symptoms, library reading studies, literature, descriptive materials, and observations that occur. The conclusion is that optimal waqf implementation requires synergy between Sharia Law, Sharia economic principles, and community ethics to achieve sustainable public welfare.